BAHAN AJAR BAHASA INDONESIA RANAH SOSIAL BUDAYA BAGI PENUTUR ASING (BIPA) - Arisul Ulumuddin; Agus Wismanto (Universitas PGRI Semarang, 2014)
Interest in foreign learners learn Indonesian poorly supported by the availabilityof teaching materials on the market. Therefore, the need for teaching materials BIPA asbalancing the amount of interest a foreign nation to learn Indonesian. In addition,teaching materials are very beneficial for the BIPA BIPA program for the teachingmaterials BIPA socio-cultural sphere we can put the wealth of identity, character, andour culture as a nation of Indonesia. Until now interactive learning books BIPA notdevelop optimally in Indonesia. One of the obstacles the development of interactivelearning media is less interactive media development technology mastered by theteachers and managers of BIPA in Indonesia. From the development of teachingmaterials BIPA social sphere obtained integrative teaching materials prepared andtailored to the learner's ability BIPA primary and secondary level, the aim of learningIndonesian to improve kemunikatif. Therefore, all material in this teaching materialaims to train the Indonesian language communicative ability for learners to be inIndonesia. Not to forget, an integrative model of teaching materials BIPA intermediatelevel presents records as a social and cultural responsibility of teachers in maintainingthe character and identity of Indonesia. in addition, and learning new vocabulary wordsthat exist in this teaching material can be fully used in everyday life.Keywords: teaching materials, BIPA, social sphere